GRAF FUZZY REGULER DAN HUBUNGANNYA DENGAN GRAF FUZZY REGULER TOTAL - Natalia, Priskila Denny; Ratnasari, Lucia (MATEMATIKA, 2011)
Fuzzy graph is a graph consists pairs of vertex set and edge set that have degree of membership containing closed interval of real number [0,1] on each edge and vertex. Regular fuzzy graph and totally regular fuzzy graph were defined by A.Nagoor Ghani and K.Radha. This paper studied the definitions of regular fuzzy graph and totally regular fuzzy graph. Next, showed that a necessary and sufficient condition under which regular fuzzy graph and totally regular fuzzy graph were equivalent